The firm tries to maximize profits $\Pi$ \begin{align} \max_{K,L}\{\Pi(K,L) = F(K,L) - RK - wL\} \end{align} where $F$ is the linear homogeneous production function, $R$ the rental rate of capital $K$ and $w$ the rental rate (wage) of labor $L$. FOCs are given by \begin{align} \Pi_K &= 0 \Leftrightarrow R = F_k\\ \Pi_L &= 0 \Leftrightarrow w = F_L. \end{align} Footnote 1 of page 33 in Acemoglu (2009) tells us that the FOCs can also derived by cost minimization.

enter image description here

With (2.6) and (2.7) being $w=F_L$ and $R=F_K$ respectively. The firm tries to minize costs \begin{align} &\min_{K,L}\{RK + wL\}\\ \text{s.t.}~~& F(k,L) = Y \end{align} where $Y$ is some output level. Set up Lagrangian \begin{align} \mathcal{L} = RK + wL + \lambda(F(K,L) - Y) \end{align}

FOCs are given by \begin{align} \mathcal{L}_K = 0& \Leftrightarrow R + \lambda F_K = 0\\ \mathcal{L}_L = 0& \Leftrightarrow w + \lambda F_L = 0\\ \mathcal{L}_\lambda = 0& \Leftrightarrow F(K,L) - Y = 0 \end{align}

  • I don't see, how we can conjecture $R = F_K$ and $w = F_L$ from those conditions?
up vote 3 down vote accepted

If $F(K,L)$ is a homogeneous function of degree one then so is $$ \Pi(K,L) = F(K,L) - R \cdot K - w \cdot L. $$ This follows straight from the definition of homogeneity. (A definition of homogeneous function can be found here.) This means that if a maximal profit exists it is zero. Otherwise you could increase all inputs by say 100%, thereby increasing both revenues and costs and thus profits by 100%. So $\Pi(K^*,L^*) = 0$.

By Euler's Homogeneous Function Theorem we have $\forall K,L$:

\begin{align} \Pi(K,L) &= \Pi_K(K,L) \cdot K + \Pi_L(K,L) \cdot L \\ \Pi(K,L) &= (F_K(K,L) - R) \cdot K + (F_L(K,L) - w) \cdot L. \end{align}

Since $\Pi(K^*,L^*) = 0$, we have $$ -(F_K(K^*,L^*) - R) \cdot K^* = (F_L(K^*,L^*) - w) \cdot L^* $$ We know that $K^*,L^* \geq 0$, so if we can show that the signs of $(F_K(K^*,L^*) - R)$ and $(F_L(K^*,L^*) - w)$ match we will have proven them to be equal to zero. Otherwise one side of the equation would be negative and the other positive. From cost minimization you have \begin{align} R + \lambda F_K & = 0\\ w + \lambda F_L & = 0. \end{align} If $\lambda >1$ then \begin{align} F_K(K^*,L^*) - R & < 0\\ F_L(K^*,L^*) - w & < 0, \end{align} if $\lambda =1$ then \begin{align} F_K(K^*,L^*) - R & = 0\\ F_L(K^*,L^*) - w & = 0. \end{align} and if $\lambda <1$ then \begin{align} F_K(K^*,L^*) - R & > 0\\ F_L(K^*,L^*) - w & > 0, \end{align}

so the signs do indeed match, hence \begin{align} F_K(K^*,L^*) - R & = 0\\ F_L(K^*,L^*) - w & = 0. \end{align}

  • Sorry, added the linear homogeneinty of $F$. Actually I'd like to show the reverse case. Is it possible to get the profit maximization conditions $R = F_K$ and $w = F_L$ from cost minimization, as Acemoglu claims? Here you show that the cost minimization conditions can be obtained from profit maximization. – clueless Oct 21 '15 at 13:15
  • @clueless Yes, and I think my answer covers this, but I will edit to clarify. – denesp Oct 21 '15 at 14:04

Your Answer

 

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.